Which of the following equation(s) are equivalent to y − 4 = 2/3(x − 1)?
A y= 2/3x - 10/3
B y= 2/3x - 3 1/3
C y= 2/3x + 3
D y= 2/3 + 10/3

Respuesta :

Answer:

  • D) y = 2/3x + 10/3

Step-by-step explanation:

Given

Equation of the line in point-slope form:

  • y  - 4 = 2/3(x - 1)

Convert the equation into slope-intercept form of y = mx + b:

  • y - 4 = 2/3(x - 1)
  • y - 4 = 2/3x - 2/3
  • y = 2.3x + 4 - 2/3
  • y = 2/3x + (12 - 2)/3
  • y = 2/3x + 10/3

Correct choice is D

Answer:

[tex]\textsf{D.} \quad y=\dfrac{2}{3}x+\dfrac{10}{3}[/tex]

Step-by-step explanation:

Given equation:

[tex]y-4=\dfrac{2}{3}(x-1)[/tex]

Distribute the parentheses on the right side of the equation:

[tex]\implies y-4=\dfrac{2}{3}x-\dfrac{2}{3}[/tex]

Add 4 to both sides:

[tex]\implies y-4+4=\dfrac{2}{3}x-\dfrac{2}{3}+4[/tex]

[tex]\implies y=\dfrac{2}{3}x-\dfrac{2}{3}+4[/tex]

Rewrite 4 as 12/3:

[tex]\implies y=\dfrac{2}{3}x-\dfrac{2}{3}+\dfrac{12}{3}[/tex]

[tex]\implies y=\dfrac{2}{3}x+\dfrac{12}{3}-\dfrac{2}{3}[/tex]

[tex]\textsf{Apply the fraction rule} \quad \dfrac{a}{c}-\dfrac{b}{c}=\dfrac{a-b}{c}:[/tex]

[tex]\implies y=\dfrac{2}{3}x+\dfrac{12-2}{3}[/tex]

[tex]\implies y=\dfrac{2}{3}x+\dfrac{10}{3}[/tex]

Therefore, the equation that is equivalent to the given equation is:

[tex]\boxed{y=\dfrac{2}{3}x+\dfrac{10}{3}}[/tex]

ACCESS MORE